Evaluation of permanent deformation of unmodified and rubber-reinforced SMA asphalt mixtures using dynamic creep test - Katman H.Y.; Ibrahim M.R.; Karim M.R.; Salim Mashaan N.; Koting S. (Hindawi Publishing Corporation, 2023)
Asphalt; Asphalt mixtures; Crosslinking; Deformation; Mixtures; Reinforcement; Rubber; Creep behaviour; Creep strain; Cross linking agents; Dynamic creeps; Permanent deformations; Polyoctenamer; Stress levels; Ultimate strain; Creep